2022
DOI: 10.1088/1361-6501/aca34a
|View full text |Cite
|
Sign up to set email alerts
|

Low-pass U-Net: a segmentation method to improve strip steel defect detection

Abstract: The detection of strip steel surface defects is critical to ensure the quality of strip steel productions. At present, many deep-learning-based methods have been presented and achieve outstanding performance. However, most of these methods ignore the frequency information among defect areas, which plays an important role in defect detection. This paper proposes a deep learning method to further improve defects segmentation effect based on existing methods, called Low-Pass U-Net. Since most defects on strip ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Pratt et al [24] used the U-Net semantic segmentation model for defective image segmentation of solar photovoltaic modules, and the algorithm achieved a high recall rate of 84%, 69%, and 53% for inactive, cracked, and gridline defects, respectively. Liu et al [25] used the improved U-Net network to segment the surface defects of strip steel, and the experimental results showed that the Dice metrics, mIoU and Recall reached 0.903, 0.865, and 0.912, respectively. These methods demonstrate that semantic segmentation has achieved commendable results in various industrial domains, indicating its feasibility for application in the detection of WR surface defects.…”
Section: Referencesmentioning
confidence: 99%
“…Pratt et al [24] used the U-Net semantic segmentation model for defective image segmentation of solar photovoltaic modules, and the algorithm achieved a high recall rate of 84%, 69%, and 53% for inactive, cracked, and gridline defects, respectively. Liu et al [25] used the improved U-Net network to segment the surface defects of strip steel, and the experimental results showed that the Dice metrics, mIoU and Recall reached 0.903, 0.865, and 0.912, respectively. These methods demonstrate that semantic segmentation has achieved commendable results in various industrial domains, indicating its feasibility for application in the detection of WR surface defects.…”
Section: Referencesmentioning
confidence: 99%
“…Experimental results on industrial datasets demonstrated successful metal defect detection under various conditions. In a similar vein, Liu et al 8 proposed a low-pass U-Net to enhance existing methods for detecting and segmenting surface defects in steel strips. By applying an adaptive variance Gaussian low-pass filter before downsampling in the encoder, aliasing is prevented, and high-frequency information is separated, leading to improved defect segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, many researchers have extended the application of object detection methodologies to other fields such as airborne object detection, 3D detection, and medical detection. All of these works have contributed to the advancement of the defect detection sector [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%